2016
DOI: 10.3390/nu8100601
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc and Selenium Supplementation Mode on Their Bioavailability in the Rat Prostate. Should Administration Be Joint or Separate?

Abstract: It is thought that zinc and selenium deficiency may play a significant role in the etiology of prostate cancer. Although joint zinc and selenium supplementation is frequently applied in the prevention of prostate diseases, the bioavailability of these elements in the prostate after co-administration is still unknown. The study examines the effect of subchronic supplementation of zinc gluconate and selenium compounds (sodium selenite or selenomethionine), administered together or separately, on their bioavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Our findings confirm those of our previous work, indicating that simultaneous administration of Zn with Se may be not beneficial. Se affects the bioavailability of Zn to the prostate [22] and, as indicated in the present paper, it seems to suppress the effects of Zn on steroid hormone levels and AR protein expression in the prostate gland of rats. Therefore, the following conclusions can be drawn: firstly, Zn administration alone leads to an increase in T concentrations accompanied by an increase in the protein expression of AR in both parts of the prostate; secondly, combined administration of Zn and Se eliminates the effect of Zn on the protein expression of AR in the prostate and the serum concentration of steroid hormones in supplemented animals, which may suggest that the two elements act antagonistically; finally, Se supplementation alone results in the same level of AR protein expression in administration and 90 days after administration periods.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our findings confirm those of our previous work, indicating that simultaneous administration of Zn with Se may be not beneficial. Se affects the bioavailability of Zn to the prostate [22] and, as indicated in the present paper, it seems to suppress the effects of Zn on steroid hormone levels and AR protein expression in the prostate gland of rats. Therefore, the following conclusions can be drawn: firstly, Zn administration alone leads to an increase in T concentrations accompanied by an increase in the protein expression of AR in both parts of the prostate; secondly, combined administration of Zn and Se eliminates the effect of Zn on the protein expression of AR in the prostate and the serum concentration of steroid hormones in supplemented animals, which may suggest that the two elements act antagonistically; finally, Se supplementation alone results in the same level of AR protein expression in administration and 90 days after administration periods.…”
Section: Discussionsupporting
confidence: 66%
“…Our present findings indicate that supplementation of rats with Zn significantly increases AR protein expression in both lobes of the prostate, but also that this effect was noted in the DL lobe only after 90 days of administration. It has previously been found that administration of Zn gluconate results in the accumulation of Zn in prostate tissue [22], which then inhibits the conversion of T to DHT by the inhibition of 5α-reductase. Similarly, the rats in the present study demonstrated increased serum T concentration, but not DHT concentration, which may have been associated with the presence of high Zn levels and greater AR protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that part of the supplemented selenium would have passed though different routes in addition to replenishing the serum component. Among such possible selenium channeling routes may include, excretion [54]; metabolism by gut biota to forms that reduce absorption into circulation [55]; used up for toxicity modulation [56]; channeled towards other tissue optimization [57] including that of the prostate [58][59][60]; or the selenomethionine component in the selenized yeast [61] getting non-specifically incorporated into a wide range of tissue proteins in place of methionine [62,63]. Takata et al, 2009 have shown that serum selenium level is a reflection of the levels in the prostate [59].…”
Section: Discussionmentioning
confidence: 99%